2014
DOI: 10.1021/ja4104217
|View full text |Cite
|
Sign up to set email alerts
|

Quantum Mechanical/Molecular Mechanical Free Energy Simulations of the Self-Cleavage Reaction in the Hepatitis Delta Virus Ribozyme

Abstract: The hepatitis delta virus (HDV) ribozyme catalyzes a self-cleavage reaction using a combination of nucleobase and metal ion catalysis. Both divalent and monovalent ions can catalyze this reaction, although the rate is slower with monovalent ions alone. Herein, we use quantum mechanical/molecular mechanical (QM/MM) free energy simulations to investigate the mechanism of this ribozyme and to elucidate the roles of the catalytic metal ion. With Mg2+ at the catalytic site, the self-cleavage mechanism is observed t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

12
153
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 70 publications
(167 citation statements)
references
References 61 publications
12
153
0
Order By: Relevance
“…The observed concerted coupled proton transfer appears to be a general mechanism in enzymes that catalyzes phosphate transfer and cleavage reactions. 43,76,[95][96][97][98] Our calculations also provided evidence that the specific metal ion coordination mode may play a prominent role in the catalytic reaction. We developed a new implementation to quantitatively determine the symmetry around the metal ion during the catalytic reaction.…”
Section: Discussionmentioning
confidence: 54%
“…The observed concerted coupled proton transfer appears to be a general mechanism in enzymes that catalyzes phosphate transfer and cleavage reactions. 43,76,[95][96][97][98] Our calculations also provided evidence that the specific metal ion coordination mode may play a prominent role in the catalytic reaction. We developed a new implementation to quantitatively determine the symmetry around the metal ion during the catalytic reaction.…”
Section: Discussionmentioning
confidence: 54%
“…The calculations have provided a detailed catalytic pathway partially consistent with experimental data as well as some specific mechanistic predictions. These simulations predicted a change from a concerted mechanism when the active site Mg 2+ is present to a stepwise pathway (via a protonated phosphorane intermediate) in the presence of Na + and absence of Mg 2+ (Ganguly et al 2014). The work presented here provides a detailed computational perspective on active site Mg 2+ association and its contribution to catalysis.…”
Section: Introductionmentioning
confidence: 94%
“…As such, we proceed under the assumption that C75 is protonated in all states considered here. In the present work, as in that of Ganguly et al (2014), the deprotonation step is assumed to have already occurred before the reaction proceeds (i.e., during the QM/MM simulation). Instead, preequilibrium assumptions are used to estimate the fraction of active enzyme from the relative free energies (calculated by MM/3D-RISM) of the various unreacted states (i.e., combinations of Mg 2+ bound/unbound and O2…”
Section: Hdvr Ground Statesmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, experimental studies and theoretical calculations have suggested that the nucleophile is activated in the HDV ribozyme through a divalent cation located in the active site, which can be partially hydrated, and would serve either as a Lewis acid, a Brønsted base or both [13,14]. In the case of the hammerhead, experimental and computational studies suggest that an adenine (A38) and a guanine (G8) have an important role in the catalytic mechanism, the later acting as an acid ("AH" in Scheme 1) whose hydroxyl O2′ is activated by the presence of a Mg 2+ cation [15,16].…”
mentioning
confidence: 99%